Predictive Factors for Successful Colonic Stenting in Acute Large-Bowel Obstruction. Issue 3 (March 2015) - Boyle, Derek J.; Thorn, Christopher; Saini, Ashish; Elton, Colin; Atkin, Gary K.; Mitchell, Ian C.; Lotzof, Kevin; Marcus, Adrian; Mathur, Pawan
<x xml:space="preserve">Abstract</x> BACKGROUND: Colonic stenting has failed to show an improvement in mortality rates in comparison with emergency surgery for acute large-bowel obstruction. However, it remains unclear which patients are more likely to benefit from this procedure. OBJECTIVE: The aim of this study is to identify factors that may be predictive of successful outcome of colonic stenting in acute large-bowel obstruction. DESIGN: All patients undergoing colonic stenting for acute large-bowel obstruction between 1999 and 2013 were studied. The demographics and characteristics of the obstructing lesion were analyzed. SETTINGS: This investigation was conducted at a district general hospital. PATIENTS: A total of 126 (76 men; median age, 76 y; range, 42–94 y) with acute large-bowel obstruction were included in the analysis. INTERVENTION: The insertion of a self-expanding metal stent was attempted for each patient to relieve the obstruction. MAIN OUTCOME MEASURES: The primary outcomes measured were technical success in the deployment of the stent, clinical decompression, and perforation rates. RESULTS: Technical deployment of the stent was accomplished in 108 of 126 (86%) patients; however, only 89 (70%) achieved clinical decompression. Successful deployment and clinical decompression was associated with colorectal cancer (p = 0.03), shorter strictures (p = 0.01), and wider angulation distal to the obstruction (p = 0.049). Perforation was associated with longer strictures (p = 0.03) LIMITATIONS: This study was limited by its retrospective nature. CONCLUSION: Colonic stenting in acute large-bowel obstruction is more likely to be successful in shorter, malignant strictures with less angulation distal to the obstruction. Longer benign strictures are less likely to be successful and may be associated with an increased risk of perforation.